MITOS PADA LOGO KABUPATEN BOGOR SPORT AND TOURISM - Qoute Nuraini Cahyaningrum; Sari Rejeki (SEMIOTIKA: Jurnal Komunikasi, 2022)
This research discusses the myths in the Bogor Sport and Tourism Regency Logo. This research uses qualitative research methods . The object of this research is the logo of Bogor Sport and Tourism Regency which was inaugurated in 2019. This logo displays the shape of mountains, kujang, taro, paragliding sports. This research uses documenter data collection techniques, visual material data collection techniques and online data techniques. The study used semiotics data analysis methods or techniques with an approach from Barthes that analyzed the meanings of denotation, connotations and myths. The technique of examining the validity of research results uses a cycle of data similarity, research persistence. And triangulation theory, the theory used is the theory of Symbolic Interactionism of Mead and Blumer. The results of the research obtained from this study related to the myth in the logo of Bogor Sport and Tourism Regency is that the Bogor Regency government wants to convey the message that currently the Bogor Regency government is having a strong goal and spirit to advance Bogor Regency towards The City of Sport and Tourism.Â  Bogor Regency Government relies on the potential of its territory to be part of tourism and sports activities. Beautiful landscapes, sports facilities, community culture and unique processed food become important points that are "sold" in the progress of Bogor Regency in the Sport & Tourism sector.